1995
DOI: 10.1001/archpsyc.1995.03950240058011
|View full text |Cite
|
Sign up to set email alerts
|

Signs of Defensive Control Locate Conflicted Topics in Discourse

Abstract: The findings support the psychodynamic hypothesis that observation of defensive behaviors may locate times of communication about conflicted themes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…A group of reviewing clinicians decided that this session was exemplary in containing in clear form a prototype of her key conflicts. Furthermore, Session 12 has two 5-min segments showing signs of defensive control that are seen as being key moments (Horowitz, Milbrath, & Stinson, 1995). To allow a better understanding, I summarize the first 11 sessions as follows: The patient was describing the good properties of her late husband James throughout the first 10 sessions.…”
Section: Methodsmentioning
confidence: 99%
“…A group of reviewing clinicians decided that this session was exemplary in containing in clear form a prototype of her key conflicts. Furthermore, Session 12 has two 5-min segments showing signs of defensive control that are seen as being key moments (Horowitz, Milbrath, & Stinson, 1995). To allow a better understanding, I summarize the first 11 sessions as follows: The patient was describing the good properties of her late husband James throughout the first 10 sessions.…”
Section: Methodsmentioning
confidence: 99%
“…By the 1970s, the Dartmouth adaptation of the General Inquirer had been updated for more general use on mainframe computers (e.g., Rosenberg, Schnurr, & Oxman, 1990; Rosenberg & Tucker, 1979). Many other word-based text analysis programs followed, a number of which were guided by psychoanalytic themes (Bucci, 1997; Horowitz, Milbrath, & Stinson, 1995; Mergenthaler, 1996). Interestingly, the majority of studies relying on these computer-based text analysis methods focused on distinguishing medical and psychiatric diagnoses.…”
mentioning
confidence: 99%
“…First, we examined data from three subjects in a series of singlecase studies (Hart, Stinson, Field, Ewert, Horowitz, 1995;Eels, Fridhandler, & Horowitz, 1995 ;Horowitz, Fridhandler, & Stinson, 1992;Horowitz et al, 1991Horowitz et al, , 1993Horowitz et al, , 1994Horowitz, Milbrath, & Stinson, 1995). In each case, we found that grief-related psychopathology was associated with a combination of contradictory role beliefs, leading to potentials for intense but dreaded emotional states and excessive regulation of emotional information processing to ward off these states.…”
Section: Horowitz Et Almentioning
confidence: 98%